First footprints people, land and resources in Aotearoa - Adds, Peter; Wood, Bronwyn (Tangata Whenua, 2010)
Resource for year 9 to 11 students covering the early settlement of New Zealand, including Māori migration, settlement, life and interaction in various areas of New Zealand over time, the physical environment of New Zealand and how people interact with the landscape, and changing patterns of resource and land use. Suggested level: junior secondary